Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1046/j.1469-7580.2001.19950585.x
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic splanchnic nerves: implications for splanchnic denervation

Abstract: Splanchnic neurectomy is of value in the management of chronic abdominal pain. It is postulated that the inconsistent results of splanchnicectomies may be due to anatomical variations in the pattern of splanchnic nerves. The advent of minimally invasive and video-assisted surgery has rekindled interest in the frequency of variations of the splanchnic nerves. The aims of this study were to investigate the incidence, origin and pattern of the splanchnic nerves in order to establish a predictable pattern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 7 publications
1
29
0
Order By: Relevance
“…In the present study the common origin was from the 11 th ganglion in 17 specimens (27%) and from the 12 th ganglion in 7 specimens (11%). Some authors observed in his findings the intermediate splanchnic ganglia (ISG) was observed only on the GSN main trunk with an incidence of 6 out of 10 sides (60%) in the adult cadavers and 11 of 28 sides (39%) in the fetuses [7]. In the present study intermediate splanchnic ganglion was observed in 13 of 62 (21%) sides in adult cadavers on the GSN.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…In the present study the common origin was from the 11 th ganglion in 17 specimens (27%) and from the 12 th ganglion in 7 specimens (11%). Some authors observed in his findings the intermediate splanchnic ganglia (ISG) was observed only on the GSN main trunk with an incidence of 6 out of 10 sides (60%) in the adult cadavers and 11 of 28 sides (39%) in the fetuses [7]. In the present study intermediate splanchnic ganglion was observed in 13 of 62 (21%) sides in adult cadavers on the GSN.…”
Section: Discussionmentioning
confidence: 50%
“…In the present study in 11 cases 11 ganglia were present bilaterally; an accessory ganglion connecting with the subcostal nerve was present in three cadavers bilaterally and in one cadaver unilaterally. The origin of splanchnic nerves differs considerably with respect to their number, the level at which the thoracic ganglia gives off their fibers to the individual thoracic splanchnic nerves, the presence of the lesser and least nerves and accessory nerve fibers [5][6][7][8]. There were three splanchnic nerves of the thoracic sympathetic trunk; arising from the lower eight ganglia.…”
Section: Discussionmentioning
confidence: 99%
“…A higher origin of the greater splanchnic nerve at the level of T4 has been reported (Kuntz, 1934 andReed, 1951) but in the present study, we report the same at a higher level i.e T3 . To the best of our knowledge, only a single study in the past has reported a higher origin of greater splanchnic nerve at T3 level, but it was not supplemented with necessary histological study (Naidoo et al, 2001). There are past reports of a common trunk for the greater and lesser splanchnic nerves (Naidoo et al) but our study showed a common trunk of greater, lesser and least splanchnic nerves after each of them had originated separately from MSC.…”
Section: Discussionmentioning
confidence: 99%
“…This operation is used in the treatment of the nagging pain in chronic pancreatitis and pancreatic cancer (Naidoo et al) . The success of the sympathetic denervation procedure depends upon the presence or absence of visible or barely perceptible accessory ganglia and pathways other than those classically described (Naidoo et al;Hoffmann;Kuntz & Alexander, 1950;Ehrlich & Alexander, 1951). The region of second thoracic ganglion is considered as a key ganglion for any sympathectomy (Ramsaroop et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the celiac ganglia are functionally related to the splanchnic nerves [4]. The splanchnic nerves contain the visceral efferent fibers but also pain-conducting visceral afferent fibers [5,6] and transmit the majority of nociceptive information www.fhc.viamedica.pl from the viscera. Clinically, splanchnic nerve block may provide relief of pain in a subset of patients who fail to obtain relief from celiac plexus block [7].…”
Section: Introductionmentioning
confidence: 99%